A modern pollen data set for the forest–meadow–steppe ecotone from the Tibetan Plateau and its potential use in past vegetation reconstruction - Wang, Nannan; Liu, Lina; Zhang, Yanrong; Cao, Xianyong (Boreas, 2022)
The relationship between modern pollen and vegetation provides the basis for the interpretation of stratigraphic pollen assemblages and the quantitative reconstruction of past vegetation. We selected 168 topsoil samples from four different vegetation types on the south‐eastern Tibetan Plateau to explore the relationships between pollen assemblages, vegetation and climate. The results reveal that pollen assemblages discriminate the vegetation types well; the subalpine coniferous and evergreen broad‐leaved forest is characterized by a high proportion of arboreal taxa (e.g. Pinus, Picea, Betula); the alpine shrub and meadow and alpine steppe vegetation types are dominated by Cyperaceae, followed by Artemisia and Brassicaceae; and the alpine steppe‐shrub is characterized by a high percentage of Artemisia, with Cyperaceae, Asteraceae and Brassicaceae as common taxa. Redundancy analysis shows that mean temperature of the coldest month (Mtco) is the main climatic factor that influences pollen distribution. Pollen diversity indices (including richness and evenness) gradually decrease from SE to NW. The random forest classification has good performance in distinguishing vegetation types. Our study supplies a comparatively detailed description of the relationship between the pollen assemblage and vegetation in the forest–meadow–steppe ecotone on the south‐eastern Tibetan Plateau. In addition, the random forest model has potential application for reconstructing the past vegetation type of the fossil pollen spectra on the south‐eastern Tibetan Plateau.